Photocatalytic degradation of textile dyes on Cu2O-CuO/TiO2 anatase powders. Issue 2 (June 2016) - Ajmal, A.; Majeed, I.; Malik, R.N.; Iqbal, M.; Nadeem, M. Arif; Hussain, I.; Yousaf, S.; Zeshan,; Mustafa, G.; Zafar, M.I.; Nadeem, M. Amtiaz
Graphical abstract: Highlights: Non noble metal supported Cu2 O-CuO/TiO2 catalysts have been prepared and characterized. Photodegradation of textile dyes on Cu2 O-CuO/TiO2 is studied. TiO2 anatase is preferred over P25 as former can be obtained with much higher surface area. Abstract: TiO2 anatase photocatalysts with ca. 2, 4 and 8 wt.% copper metal loading have been employed for the photocatalytic degradation of textile dyes (one of the major contaminants in effluent from textile industries around the world) and their degradation efficiencies compared with benchmark Degussa P25. In order to investigate their surface and bulk composition, all catalysts were characterized using XRD, UV–vis, XPS and TEM techniques. TEM and XPS results confirmed the presence of Cu in its oxide form (Cu2 O-CuO). Under optimized conditions (i.e. catalyst dose of 125 mg L −1 and initial dye concentration of 5 mg L −1 ), Degussa P25 showed 76% degradation efficiency for primary reactive blue 49 (RB 49) dye in 80 min. However, under the same optimized conditions, a complete primary RB 49 dye removal was observed at ca. 4 wt.% Cu2 O-CuO/TiO2 catalyst. Kinetics analysis of photodegradation ( kd ) nearly followed a pseudo-first-order kinetic model with a regression coefficient (R 2 ) value in the range of 0.97–0.86 for 4 wt.% Cu2 O-CuO/TiO2 catalyst. These results indicate that non noble supported TiO2 anatase may be a better choice for photocatalytic dye degradation as compared to other commercially available photocatalysts.